An Introduction to Husserl's phenomenology. - Patocka, Jan. (Chicago, Illinois : Open Court, 1996)
Patocka's celebrated Introduction, here made available in English for the first time, is not an introduction in the ordinary sense of the term. Patocka ranges over the whole of Husserl's output, from The Philosophy of Arithmetic to The Crisis of the European Sciences, and traces the evolution of all the central issues of Husserlian phenomenology--intentionality, categorial intuition, temporality, the subject-body; the concrete a priori, and transcendental subjectivity. But rather than attempting to give a tour of Husserl's workshop, Patocka is himself hard at work on Husserl's problems.
eBooks on EBSCOhost
Keywords: Husserl, Edmund, -- 1859-1938.; Husserl, Edmund, -- 1859-1938; Phenomenology; Phénoménologie.; phenomenology; PHILOSOPHY / History & Surveys / Modern; Phenomenology